Nonfullerene Tandem Organic Solar Cells with High Performance of 14.11 - Zhang, Yamin; Kan, Bin; Sun, Yanna; Wang, Yanbo; Xia, Ruoxi; Ke, Xin; Yi, Yuan‐Qiu‐Qiang; Li, Chenxi; Yip, Hin‐Lap; Wan, Xiangjian; Cao, Yong; Chen, Yongsheng (Advanced materials (Weinheim), 2018)
Fabricating solar cells with tandem structure is an efficient way to broaden the photon response range without further increasing the thermalization loss in the system. In this work, a tandem organic solar cell (TOSC) based on highly efficient nonfullerene acceptors (NFAs) with series connection type is demonstrated. To meet the different demands of front and rear sub‐cells, two NFAs named F‐M and NOBDT with a whole absorption range from 300 to 900 nm are designed, when blended with wide bandgap polymer poly[(2,6‐(4,8‐bis(5‐(2‐ethylhexyl)thiophen‐2‐yl)‐benzo[1,2‐b:4,5‐b′]dithiophene))‐alt‐(5,5‐(1′,3′‐di‐2‐thienyl‐5′,7′‐bis(2‐ethylhexyl)benzo[1′,2′‐c:4′,5′‐c′]dithiophene‐4,8‐dione))] (PBDB‐T) and narrow bandgap polymer PTB7‐Th, respectively, the PBDB‐T: F‐M system exhibits a high Voc of 0.98 V and the PTB7‐Th: NOBDT system shows a remarkable Jsc of 19.16 mA cm−2, which demonstrate their potential in the TOSCs. With the guidance of optical simulation, by systematically optimizing the thickness of each layer in the TOSC, an outstanding power conversion efficiency of 14.11%, with a Voc of 1.71 V, a Jsc of 11.72 mA cm−2, and a satisfactory fill factor of 0.70 is achieved; this result is one of the top efficiencies reported to date in the field of organic solar cells. A non‐fullerene tandem organic solar cell (OSC) with high efficiency is fabricated. Two non‐fullerene acceptors named F‐M and NOBDT with a whole absorption range from 300–900 nm are designed for the front and rear sub‐cell respectively; the tandem cell based on them demonstrates an outstanding PCE of 14.11%, which is among the top PCEs in the field of OSCs.